2022
DOI: 10.1002/nag.3464
|View full text |Cite
|
Sign up to set email alerts
|

Two‐phase model for the excavation analysis in partially saturated soft soils using the particle finite element method

Abstract: A two-phase velocity-pressure stabilized formulation is proposed for the numerical analysis of mechanized excavations in partially saturated soft soils using the Particle Finite Element Method (PFEM). The fully coupled formulation is based on the theory of porous media in association with the Soil Water Characteristic Curve and the porosity-dependent Kozeni-Carman model for the realistic estimation of the soil permeability. The combination of the PFEM methodology, characterized by a global re-meshing strategy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 101 publications
0
3
0
Order By: Relevance
“…In the geotechnical engineering field, many studies have made an effort to find soil parameters using the back‐analyses method 6 ; Yapage, et al., 7 Li, et al., 8 Goh, et al., 9 Zhou, et al., 10 Ohtsu, et al., 11,12 Tang, et al., 13 Leon Bal and Meschke 14 used the finite‐element program, for example, ABAQUS software and/or PLAXIS, for numerical modeling the soft soil improved by deep cement mixing (DCM) columns 15 . Waichita, et al 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…In the geotechnical engineering field, many studies have made an effort to find soil parameters using the back‐analyses method 6 ; Yapage, et al., 7 Li, et al., 8 Goh, et al., 9 Zhou, et al., 10 Ohtsu, et al., 11,12 Tang, et al., 13 Leon Bal and Meschke 14 used the finite‐element program, for example, ABAQUS software and/or PLAXIS, for numerical modeling the soft soil improved by deep cement mixing (DCM) columns 15 . Waichita, et al 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the complexity of geology needs to be further studied. German scholars used the finite element method [12][13][14] to simulate saturated layered soil [15]. The electricity and heat of the soil are coupled with the groundwater around the DC grounding electrode.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the PFEM has been very successfully applied to geomechanics problems. In particular, solutions to the saturated soils problems 8 and the partially saturated soils problems, 9 seismic failure of layered clayey slopes, 10 offshore geotechnical engineering problems, 11 and 3D soil flow problems. 12 A state-of-the-art review of the PFEM can be found in Cremonesi et al 13 The PFEM is actually an updated-Lagrangian approach with nodes treated as particles.…”
Section: Introductionmentioning
confidence: 99%